Concept of Manas: Insights from Nyāya Darśana and Āyurveda - Hetal Amin; Rohit Sharma; Hitesh A Vyas; Mahesh K Vyas (Wolters Kluwer Medknow Publications, 2014)
Studying a single Shāstra (treatise) is not enough to grab the true import of any concept. For a truly inter-disciplinary approach, knowledge of as many allied branches, be it from science or philosophy, is desirable. Nyāya philosophy is a system of logic or rules, whereas Āyurveda is the science of life. The relationship of Manas (~mind) to the body is accepted by both Āyurveda and Nyāya philosophy. In order to gain a better understanding of the concept of Manas, it is necessary to screen the philosophical views, which are present in ancient Āyurvedic as well as Nyāya texts. Therefore, in the current article, an attempt has been made to derive the concept of Manas from Nyāya philosophy as well as Āyurvedic science .